Late neo-assyrian officialdom - Henshaw, Richard A. (JAOS, 1980)
The publication of 33 ration lists from Nimrud, accompanied by copies of 15 related lists, is prefaced by the fullest study of late Neo-Assyrian officialdom since E. Klauber, Assyrisches Beamtentum (1910). The prominent place of the queen, and the virtual lack of mention of the king, may show that these wine rations were for her household, with the large number of officials, craftsmen, and cultic personnel listed belonging to her. The lists contain several titles previously unknown. As was the case with previous texts of this type, e.g., C. H. W. Johns, Assyrian Deeds and Documents (1898ff), Nos. 675 ff, a great number of problems emerge, and the author in dealing with these has integrated the functionaries into the total administrative life of the kingdom.